166k views
1 vote
Find the sum, the difference, the product, and the quotient of the functions f and g:

i) f(x) = 4x – 6 and g(x) = 2x^2 – 3x
ii) f(x) = x^2 - 1 and g(x) = 1 - x​

User Otolock
by
5.5k points

2 Answers

7 votes

Final answer:

To find the sum, difference, product, and quotient of two functions, we use the corresponding operations on their terms.

Step-by-step explanation:

Sum:

To find the sum of two functions, we simply add the corresponding terms. For f(x) = 4x - 6 and g(x) = 2x^2 - 3x, the sum is (4x - 6) + (2x^2 - 3x).

Difference:

To find the difference of two functions, we subtract the corresponding terms. For f(x) = 4x - 6 and g(x) = 2x^2 - 3x, the difference is (4x - 6) - (2x^2 - 3x).

Product:

To find the product of two functions, we multiply the corresponding terms. For f(x) = 4x - 6 and g(x) = 2x^2 - 3x, the product is (4x - 6)(2x^2 - 3x).

Quotient:

To find the quotient of two functions, we divide the first function by the second function. For f(x) = 4x - 6 and g(x) = 2x^2 - 3x, the quotient is (4x - 6) / (2x^2 - 3x).

User Zubia
by
5.3k points
5 votes

Answer:

is it ii)F(x)=x2

Step-by-step explanation:

User Syrkull
by
6.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.